Subject Specific Modelling of Electrical Conduction in the Body: A Case Study - Lau, Howard; Li, Qing; Ruys, Andrew John; Wang, Xiu; Carter, P. (Journal of biomimetics, biomaterials and biomedical engineering, 2011)
Modelling of bioelectric phenomena in the human body poses unique problems compared to those encountered in other fields of engineering. Accurate definition of the physical domain and material properties is difficult due to geometrical complexity and uncertainty in tissue characterisation. A workflow is presented for finite element simulation of electric current in the body. This is illustrated through an application on a subject-specific cranial model for simulation of a cochlear implant. Operations required for the full workflow include: data acquisition, image registration and segmentation, material property assignment, numerical analysis, and visualisation. The case study described uses MRI imaging and diffusion tensor MRI for definition of the analysis domain and material properties with analysis conducted in ANSYS. Image registration and segmentation were accomplished using custom designed algorithms. Visualisation was achieved using a 24-bit red-green-blue colour scheme to represent directional vectors.